166 The Protective Role of GPR39 in Subarachnoid Hemorrhage. (April 2023) - Mazur-Hart, David; Bah, Thierno; Siler, Dominic Aaron; Pike, Martin; Cetas, Justin Schultz; Alkayed, Nabil
Abstract : INTRODUCTION: Aneurysmal subarachnoid hemorrhage (SAH) is a devastating stroke with high morbidity and mortality. It causes an early brain injury (EBI), the severity of which can predict delayed cerebral ischemia (DCI). Neuroinflammation is a key component of EBI. The G protein-coupled receptor 39 (GPR39) is expressed in brain, and it has been shown to modulate neuroinflammation. METHODS: Endovascular perforation technique induced SAH in GPR39 knockout (KO) and wild-type (WT) littermate mice. Laser-Doppler was used to monitor cortical perfusion before, during, and right after SAH. Body mass and neurological deficit (neuroscore) were assessed daily after SAH. T2-weighted MRI was used to measure ventricular volumes, and T2*-weighted gradient recalled echo (GRE) MRI was used to assess cortical vein engorgement at 24 hours after SAH. Behavioral deficit was assessed using the accelerating rotarod at baseline and on days 2, 3 and 4 after SAH and balance beam on days 2, 3 and 4 after SAH. RESULTS: SAH caused an acute, communicating hydrocephalus with engorged cortical veins. WT and KO mice exhibited significant weight loss and deficits in neuroscore after SAH compared to sham mice. GPR39 KO mice had a significantly worse neuroscore than WT mice 3 days after SAH (mean 20.7 vs. 22.3; n = 12 vs. 15, respectively; p = 0.01). Additionally, GPR39 KO mice exhibited worse scores on rotarod 2 days after SAH (mean latency to fall 138.9 vs. 108.8; n=12 vs 15, respectively, p = 0.07) and balance beam 1 day after SAH (mean time to traverse 24.8 vs. 31.8; n = 8 vs. 11, respectively, p = 0.1). CONCLUSIONS: Our findings indicate that mice with GPR39 deletion exhibit worse outcomes in neuroscore and sensorimotor domains. These results suggest that GPR39 plays a protective role and may serve as a therapeutic target in SAH.